Nutrition and inflammaging : unveiling the impact of diet on healthy aging - Niken Puruhita (Indonesian Nutrition Association, 2023)
Aging is a declining process which leads to a poorer state of human health. The process involved immune system, known as immunosenescence, which is a multifactorial and dynamic process, involving both innate and acquired immunity. It is characterized by a progressive reduction in the ability to trigger immune responses against infections and vaccinations and lead to inflammaging. Immunosenescence plays a critical role in most chrocic diseases in older people, therefore, attempts are made to slow down or reverse the process.